Studying the electronic properties of the overlap between (Gallium Arsenic/Titanium Oxide) nanoclusters and (fluorine, Zinc) impurities through DFT - Ahmed; Abbas Shwya Alwan; Vladimir Valentinovich Egorov (University of Thi-Qar Journal of Science, 2025)
In this study, density functional theory (DFT) calculations have been conducted using the B3LYP hybrid functional with the 6-31G basis set. The computational procedures have been implemented via the Gaussian 09 software package to find out the molecular geometries, electrostatic potential surfaces, contour density maps, infrared spectroscopy (IR) diagnostics, density of states (DOS) schematics, and symmetry of the nanoclusters (4GaAs/2Ti₂O₃), (6GaAs/2Ti₂O₃), (4GaAs/2Ti₂O₃)-4Zn, (4GaAs/2Ti₂O₃-)4F, (6GaAs/2Ti₂O₃)-4Zn and (6GaAs/2Ti₂O₃)-4F. The electronic characteristics: HOMO energy, LUMO energy, band gap (Eg), dipole moment, polarizability, electronegativity, and electrophilicity have been evaluated for the nanoclusters under study. The contour density maps revealed the active regions in the molecular system after the overlap between the hybrid nanoclusters (GaAs/Ti₂O₃) and the impurities (fluorine, zinc). One can visualize that the (4GaAs/2Ti₂O₃)-4Zn nanocluster exhibited a band gap approximately to (0.699 eV), which is comparable to that of gallium antimonide (GaSb), which hasan energy gap of approximately (0.7 eV), indicating its potential suitability for thermophotovoltaic (TPV) systems, laser diodes, and transistor devices. Furthermore, the symmetry demonstrated that the hybrid nanocluster (4GaAs/2Ti2O3) has the point group symmetry (Cs/C1), but after the interaction with the impurities fluorine and zinc, the symmetry becomes (C1). Symmetry merit plays a vital role in optics in physics, especially the optical activity and influence on electronic transition probabilities. The doping by the impurities zinc and fluorine atoms leads to the emergence of new energy states, and this is very apparent in the diagrams of the density of states.